PENGEMBANGAN BAHAN AJAR MULTIMEDIA INTERAKTIF BERBANTU ANYFLIP DAN QUIZIZZ UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Siti Hamisah; Caska; Sri Kartikowati3 (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article presents (1) Anyflip and Quizizz-assisted interactive multimedia teaching materials on business opportunities for products or services, (2) students’ learning effectiveness using these materials, (3) students’ responses to the materials, and (4) the improvement of students' learning motivation. The research employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) to develop the learning media. The results indicate that material expert validation achieved 90% after revision (74% before revision), and media validation averaged 85%. Teacher assessments averaged 82%, while a Paired Sample t-test showed a significant improvement in students’ learning outcomes. Students found the materials engaging and easy to understand. The Wilcoxon test indicated a significant increase in learning motivation (Z = -5.280, p < 0.05) after using Anyflip and Quizizz-assisted interactive multimedia teaching materials.